Exploring Music Performance Anxiety in Indonesian Music Majors: An Analysis Based on Instrument, Gender, Experience, and School Background and Its Implications for Music Education - Hamida, Khairunnisa Putri; Dhani, Kurnia Rahmad; Satria, Eki (Universitas Negeri Makassar, 2024)
ABSTRAKKecemasan performa musik (MPA) berdampak negatif bagi performa musisi dalam jangka pendek hingga panjang. Penelitian ini mengukur MPA mahasiswa Jurusan Musik Institut Seni Indonesia Yogyakarta. MPA ditinjau dari pilihan mayor instrumen, jenis kelamin, lama pengalaman musik, dan asal sekolah (SMK Musik dan SMU). Penelitian ini menggunakan metode kuantitatif dengan subjek mahasiswa aktif Jurusan Musik ISI Yogyakarta (N = 133). Penelitian ini menunjukkan bahwa mahasiswi (perempuan) menunjukkan MPA yang lebih tinggi dibanding mahasiswa (laki-laki) (p = 0.03); tidak terdapat perbedaan kecemasan performa musik berdasarkan instrumen musik mayor, lama pengalaman bermusik, maupun asal sekolah (p > 0.05); terdapat 68% mahasiswa musik yang mengalami MPA pada tingkat medium hingga kecemasan sangat tinggi. Mahasiswa musik memiliki beberapa strategi coping untuk menghadapi MPA, namun masih terdapat beberapa mahasiswa yang masih bingung dan tidak memiliki cara untuk mengatasi MPA. Penelitian ini diharapkan dapat menjadi suatu evaluasi pada pengembangan metode belajar musik yang memperhatikan kesiapan psikologis mahasiswa musik. ABSTRACTMusic performance anxiety (MPA) harms musicians' performance in the short to long term. This research measures the MPA of music students at the Indonesian Institute of the Arts Yogyakarta. MPA was assessed based on the choice of the musical instrument, gender, length of experience, and high-school origins (SMM and SMU). This research utilizes quantitative methods with the subjects of active students of the Music Department of the Indonesian Institute of the Arts Yogyakarta (N = 133). This research concluded that female students exhibit higher anxiety levels than males (p = 0.03); there was no significant difference in music performance anxiety based on instrument major, length of musical experience, or school origin (p > 0.05). It was found that 68% of music students at the Indonesian Institute of the Arts Yogyakarta experience medium to very high levels of music performance anxiety. Music students have reported their coping strategies to deal with music performance anxiety. However, some students reported that they have no coping strategy for their anxiety. It suggests the need to consider the psychological readiness of music students when developing music learning methods.